Sustainable Food Supply Chain Research - Yamoah, Fred Amofa; Yawson, David Eshun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Sustainable Food Supply Chain Research", as a seminar collection of articles, provides theoretical and empirical scientific insights to enable sustainable food research academics, students, and practitioners to gauge the trajectory of sustainable food supply chain research, including contemporary research positions on a sustainable food supply chain around the world. Rigorously synthesizing the relevant academic literature and gold standard methods, the scientific contributions in this reprint integrate quantitative and qualitative models and tools that address the product quality framework for food supply chains, the causes of food waste within grocery retail chains, choice editing in favour of sustainable consumption in supply chains, multi-stakeholder initiatives in food supply chains, sustainability in governance in the cocoa supply chain, digitalisation for a sustainable food supply chain, logistics service quality, crop failure and supply chain dynamics in a developing country context, strategic agility in the fresh produce supply chain, and short food supply chains, among others.